PENGARUH STUKTUR KEPEMILIKAN DAN DEWAN KOMISARIS INDEPENDEN TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA DAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING - Etty M. Nasser (Media Riset Akuntansi, Auditing & Informasi, 2008)
The objective of this research are to identi6 'the direct and indirect influences of corporate governancesbucture such as, board of independent commissioner, institutional ownershi :rand manajerial ownership to the fimes value and earnings management debt as intervening variable.This research examine 37 manufacturing companies fisted in Jakarta Stock Exchange and issues waled financial statement since 2002-2004. The statistical methods used to test the hypothesis is Structural Equation Model (SEM). The empirical result of this research indicates that manajerial ownership has a positif significant and board of commissionerhas a negative significant influences to earnings management whereas institutional ownership have no influence to earnings management. The following test indicates that board of commissioner and manajerial ownership and institutional ownership have no significant influence to the firm's value. The control variable, firm's size, has a positive significant influence to earnings management whereas leverage has a negative significant influence to the firm's value. The Last test indicates that earnings management and debt have influence to the firm's value, so it can be concluded that earnings management and debt is an intervening variable.Keywords: corporate governance, earnings management, debt, firm's value, board of director, manajerial ownership, institutional